This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Consider the sum of the first and last terms of the series. Making use of the identity tan θ = cot ( 2 π − θ ) we get that tan ( 1 6 7 π ) = cot ( 1 6 π ) .
Then letting α = 1 6 π , we have
tan 2 ( 1 6 π ) + tan 2 ( 1 6 7 π ) = tan 2 α + cot 2 α = ( tan 2 α + 2 tan α cot α + cot 2 α ) − 2 tan α cot α = ( tan α + cot α ) 2 − 2 = ( cos α sin α + sin α cos α ) 2 − 2 = ( sin α cos α 1 ) 2 − 2 = ( sin 2 α 2 ) 2 − 2 = 4 csc 2 8 π − 2
Similarly, we find that tan 2 ( 1 6 2 π ) + tan 2 ( 1 6 6 π ) = 4 csc 2 4 π − 2 = 6 AND tan 2 ( 1 6 3 π ) + tan 2 ( 1 6 5 π ) = 4 csc 2 8 3 π − 2
Then
n = 1 ∑ n = 7 tan 2 ( 1 6 n π ) = [ tan 2 ( 1 6 π ) + tan 2 ( 1 6 7 π ) ] + [ tan 2 ( 1 6 2 π ) + tan 2 ( 1 6 6 π ) ] + [ tan 2 ( 1 6 3 π ) + tan 2 ( 1 6 5 π ) ] + tan 2 ( 1 6 4 π ) = ( 4 csc 2 8 π − 2 ) + 6 + ( 4 csc 2 8 3 π − 2 ) + 1 = 4 ( csc 2 8 π + sec 2 8 π ) + 3 = 4 ⎝ ⎛ sin 2 8 π cos 2 8 π cos 2 8 π + sin 2 8 π ⎠ ⎞ + 3 = 4 ⎝ ⎛ sin 2 4 π 4 ⎠ ⎞ + 3 = 4 ( 8 ) + 3 = 3 5 [Here we used csc θ = sec ( 2 π − θ ) ] [Here we used sin θ cos θ = 2 1 sin 2 θ ]